AB0902 Genetic Characterization of Hereditary Periodic Fever Syndromes: A Retrospective Cohort of 25 Patients. (15th July 2016) - Ruiz, A.; Rubio, E.; Porras, I.; Garcia-Morillo, S.; Povedano, J.
Abstract : Background: This is a descriptive study of the epidemiological, clinical and genetic characteristics of a cohort of adult patients of a health area of 975, 000 inhabitants in the south of Spain, diagnosed with hereditary periodic fever syndrome features. We contrast the mutations found in the genetic study of these with previously published data. Objectives: A retrospective analysis of medical records of patients was performed. Sex, age, ethnicity, family history, clinical manifestations, time of evolution, genetic testing, final diagnosis, treatment and therapeutic response: the following information was collected. For the diagnosis of FMF clinical criteria such Hashomer (TH) and Livneh (ACR) was choosen, besides the usual genetic study. Methods: A total of 25 patients, 13 women and 12 men, of whom 21 had altered marenostrin gene (MEFV) (11 women and 10 men) and 4 TRAPS (2 women and 2 men) were studied. Regarding the FMF; 8 patients had mutations associated with familial Mediterranean fever (6 women and 2 men); while 13 patients (8 males, 5 females) showed mutations in MEFV protein polymorphisms considered by high high frequency in healthy population. The mean age at diagnosis was 30 years and 8 patients (38%) debuted with less than 20 years. All patients met clinical criteria. A total of 25 patients, 13 women and 12 men, of whom 21 had altered marenostrin gene (MEFV) (11 women and 10 men) and 4 TRAPS (2 women and 2 men) were studied. Regarding the FMF; 8 patients had mutations associated with familial Mediterranean fever (6 women and 2 men); while 13 patients (8 males, 5 females) showed mutations in MEFV protein polymorphisms considered by high high frequency in healthy population. Two of the patients are ethnic predisposing (an Armenian Jew and a citizen of the Middle East). Genetic testing was performed in all patients. Exons 1 to 10 of MEVF gene (marenostrin) were sequenced. Total 15 patients (71%) of patients had received sometime in the course of the disease treatment with colchicine, with good response in most cases. In the case of TRAPS, 4 patients (2 men and 2 women) were diagnosed by clinic. The genetic study was performed in all patients. Exons 2, 3 and 4, encoding the extracellular domains of TNF receptor I, being the pR92Q mutation in exon 4 in 3 patients, and pP46L homozygous mutation in exon 3 in the fourth patient were sequenced, who turn pR202Q had homozygous mutation in the gene MEVF. Results: In 8 patients (38%) recurrent mutations (M694V, E148Q and I591T, I640 M), in previous publications associated with FMF found. However, the most frequent mutation was the pR202Q detected in more than half of patients. This mutation is often associated with the pE148, but only 1 of the patients had both. Because of its high prevalence in the population (>1%) is considered a polymorphism. Regarding TRAPS, both mutations found (pR92Q and p46L) are common, but with low penetrance and a controversial clinical significance, and are thought to TNFRSF1A gene variants, although not directly responsible for the syndrome. Conclusions: Genetic studies in patients with a clinical diagnosis of FMF reveal heterogeneity. This may be due to the existence of genes at present unknown. They are generated by mutating genes similar to that seen in the FMF clinical phenotype, but in some cases, as with mutations pR202Q, pR92Q and p46L are considered polymorphisms. Disclosure of Interest: None declared